Impact of metabolic syndrome on quality of life of liver transplant recipients. Issue 9 (September 2018) - Wang, Zhenshun; Li, Ning; Lin, Dongdong
Objective: The incidence of metabolic syndrome (MS) increases after liver transplantation. This study was performed to evaluate the impact of MS on patients' quality of life after liver transplantation. Methods: We collected the medical records of 152 patients during their post-liver transplantation outpatient follow-up. Quality of life was assessed using the Medical Outcomes Study 36-Item Short Form Health Survey. Data on the patients' general condition as well as MS-related indicators were assessed in all patients. Based on the MS diagnostic criteria proposed by the International Diabetes Federation in 2005, the patients were divided into two groups: those with and without MS. We then analyzed the factors influencing MS and their impact on the patients' quality of life. Results: After liver transplantation, age and underlying liver disease were significantly associated with MS and diabetes, and sex and body mass index were associated with central obesity. Central obesity affected the patients' general health (GH) score and health transition (HT) score, and hypertension affected their GH score and physical component score (PCS). Conclusions: After liver transplantation, central obesity had a negative impact on patients' GH score and HT score, and hypertension affected their GH score and PCS.